« Factio christiana »: Nouvel examen du rapport entre les premiers groupes de croyants en Christ et les associations volontaires antiques - Urciuoli, Emiliano Rubens (Apocrypha, 2011)
Why call an ecclesia « collegium »? Historians have already shown analogies and differences between the two social formations identified by Tertullian in chapter 39 of his Apologeticum. Nevertheless, a question still remains unresolved: why should a defensor fidei draw from Roman optional associations this ticklish terminology to argue for Christians’right of gathering, and to censure the absurd cruelty of persecutions? My suggestion moves from the fact that, although it is a dangerous word, collegium is the only proper category to frame a private cult, entirely free from the system of the public religion. Thus, while describing the real nature of his ritual meetings to a fictive « Other », a Christian cannot but use this term. Still he has to be very careful: collegia are under the imperial control, while Christian cult is de facto illegal. Nevertheless, in such a little space of maneuver, Tertullian elaborates a subtle strategy to escape his main legal obstacles, denouncing the perverse habits and practices of pagan banquets and displaying the brightness of a new kind of club: the collegium-corpus, or the corpus-collegium of the ecclesial body of Christ.